2015
DOI: 10.1055/s-0035-1566245
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia as a Manifestation of New-Onset Systemic Lupus Erythematosus during Pregnancy: A Case-Based Literature Review

Abstract: Introduction New-onset systemic lupus erythematosus (SLE) during pregnancy is rare and difficult to diagnose, especially in cases that manifest as preeclampsia. We report a patient with new-onset SLE that manifested as preeclampsia during pregnancy and provide a review of the literature to identify factors for a rapid diagnosis. Case A 32-year-old primigravid Japanese woman was diagnosed with severe preeclampsia and underwent emergent cesarean section at 29 weeks of gestation. Her hypertension and renal disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Miyamoto et al . found eight out of 11 patients diagnosed with new-onset SLE during pregnancy had pre-eclampsia upon initial presentation, while three developed pre-eclampsia after SLE was diagnosed 3. All cases except one, who developed SLE post-partum, had pre-eclampsia detected in the third trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Miyamoto et al . found eight out of 11 patients diagnosed with new-onset SLE during pregnancy had pre-eclampsia upon initial presentation, while three developed pre-eclampsia after SLE was diagnosed 3. All cases except one, who developed SLE post-partum, had pre-eclampsia detected in the third trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 92%
“…Studies have found that pregnant women with SLE have worse manifestations than pregnant women without SLE and due to the hormonal changes and the increase in cytokines during pregnancy this disease may only be diagnosed for the first time during pregnancy 9,10. Most women with new-onset SLE are found to have a lower frequency of common symptoms suggestive of lupus at presentation, such as fever, arthritis, arthralgia, alopecia, oral ulcers and/or hypocomplementaemia, compared to those diagnosed in a non-pregnant state 2,3. Thrombocytopaenia is reported to occur in 10–40% of cases of new-onset lupus but in all present cases platelet counts were normal 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of active lupus nephritis in pregnancy is 4% to 30%, and in a person with a history of the previous recurrence of lupus nephritis is estimated to be 20% to 30% (10). However, there are rare reports of lupus nephritis as the first manifestation of disease in pregnancy (11). The active lupus nephritis is the biggest threat to the outcome of pregnancy in women with lupus.…”
Section: Renal Involvementmentioning
confidence: 99%